Specific Features of the Mechanism of Administrative and Legal provision for the Implementation of the State’s Law Enforcement Function in the Field of Taxation - S. O. Dmytrenko (Bulletin of Kharkiv National University of Internal Affairs)
The essence of administrative and legal provision for the implementation of the state’s law enforcement function has been studied. The elements of the mechanism of administrative and legal provision for the implementation of the state’s law enforcement function in the field of taxation have been distinguished. It has been offered to include the institutional component (subjects of provision), normative component (system of administrative and legal norms establishing the principles and rules of the state’s law enforcement function in the field of taxation), principles of implementing the state’s law enforcement function in this area, forms and methods of implementation of the state’s law enforcement function and the resource component (personnel, information, material, technical provision, etc.) into the structure of this mechanism.